Pelatihan Pembuatan Biochar Sekam Padi sebagai Upaya Peningkatan Keterampilan dan Kesuburan Lahan bagi Petani Kacang Koro di Desa Lam Peudaya, Kecamatan Darussalam, Aceh Besar - Oktarina, Hartati; Jauharlina, Jauharlina; Chamzurni, Tjut; Zaitun, Zaitun; Mukhriza, Teuku (Universitas Syiah Kuala, 2025)
Most of the residents of Lampeudaya Village, Darussalam District, Aceh Besar Regency, work as farmers. These farmers, particularly those growing jack bean (Canavalia ensiformis), face the problem of low soil fertility, which impacts production. This community service activity aims to provide scientific and practical solutions to the problems faced by farmers particularly concerning low soil fertility and limited knowledge of appropriate technology. The partners involved in this program were 25 active farmers highly motivated to improve crop yields through environmentally friendly technological approaches. The implementation methods included in-service training (IST) and on-service training (OST) using a participatory approach, encompassing theoretical sessions, hands-on practice in producing biochar from rice husks, and evaluation through pre- and post-tests. The results of the activity showed a 45% increase in participants' knowledge and a high level of satisfaction with the content and delivery methods. Most participants began producing and applying biochar independently on their farms. This activity successfully enhanced the farmers technical capacity, ecological awareness, and economic potential. The activity recommends continued mentoring programs to ensure the sustainability of biochar production and its application in sustainable farming systems. This training model can be replicated in other areas with similar characteristics.